(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers conducted a study on the Factors Affecting Teenagers to Use Illegal Drugs and Alcohol in Barangay San Jose Rodriguez Rizal to prevent someone from doing something harmful that will have major consequences before it occurs. The most common factors in using Illegal drugs and alcohol are family background and peers. The researchers used descriptive studies in their study, Factors Affecting Teenagers to Use Illegal Drugs and Alcohol at Barangay San Jose Rodriguez Rizal. Descriptive research is one in which data is gathered without causing any environmental changes (i.e., nothing is manipulated). These investigations are sometimes called " correlational " or " observational " studies. The family is the most important factor influencing a teenager’s decision to use illegal drugs and alcohol because of a lack of quality time; peer pressure is also a factor, and the community or surroundings are the third factors influencing a teenager’s decision to use illegal drugs and alcohol in barangay San Jose Rodriguez. The researchers have arrived at the following conclusions based on the summary of findings: According to the respondent, the family of the interpreted is very effective in the result. The peers interpreted it as effective. The community interpreted it as a moderately effective solution. Family quality is the most common element, causing teenagers to use illegal drugs and alcohol. The following recommendations are made based on the findings and conclusions. The Rizal family of Barangay San Jose Rodriguez Rizal provides direction and care to the teenagers. San Jose Rodriguez has pledged to abstain from using illegal drugs and alcohol.